The Importance of Book Culture for Europe - Raabe, Paul (Knygotyra, 2002)
The article reviews a thousand years of the development of book culture, analyses main factors and changes that influenced it. It investigates the issue of the present and future role of the book culture in Europe. The author defines the concept of the book culture. The term was coined 20 years ago as an antonym to the concept of the new media. It includes everything that is related to the book: writing (registering thoughts, cognition, innovation and knowledge), ideas of books and their realisation, everything related to the author and authorship. The essence of the book culture is the production, distribution, consumption of the book and all the activity of book producers of any kind. It includes everything related to the book market as well as reading. Book culture has historical and contemporary dimensions. It is investigated within the situation, which is characterized as a crisis of a book. ln fact the age of crisis has turned into the period of highest boom of the book not oniy in Germany but all over Europe. It witnesses richness of ideas and the possibilities to implement them as was never seen before. The authority of the book is growing together with the modernization of the world. The task of the historians of a book is to investigate the book culture. The main provisions of the article are made on the basis of Germany, but they could be applied to other European states. The book culture is conceived as a whoie, though it incorporates specific problems.